MODIFIKASI KIMIA KARET ALAM SIKLIS (CYCLIC NATURAL RUBBER/CNR) DENGAN TEKNIK GRAFTING: MENGGUNAKAN MONOMER METIL METAKRILAT DAN INISIATOR BENZOIL PEROKSIDA - M. Said Siregar; Muhammad Thamrin; Basuki WS; Eddiyanto , (AGRIUM: Jurnal Ilmu Pertanian, 2012)
AbstractThe research of grafting methyl methacrylate (MMA) onto Cyclic Natural Rubber (CNR) has been carried out. Benzoyl Peroxide (BPO) was used as a inisiator and temperature condition at 90oC with variation of time 1 and 2 hours. Grafting process was done with technique of reflux in a tree-neck flask  with condenser and oil bath. Spectra analysis FTIR performed for determine the presence of grafted MMA on the backbone of CNR. The results showed that the product CNR-g-MMA was formed with the marked appearance of the absorption peak wave numbers at 1731 and 1730 cm-1 (carbonyl group absorption) typical for carbonyl (C = O) of metal methacrylate. The degree of grafting increased with the increasing time grafting.Keywords: grafting, cyclic natural rubber, mathylmetacrilate, benzoyl peroxide